Cannabidiol plasma determination and pharmacokinetics conducted at beginning, middle and end of long-term supplementation of a broad-spectrum hemp oil to healthy adult dogs - Corsato Alvarenga, Isabella; Gustafson, Daniel; Banks, Krista; Wilson, Kim; McGrath, Stephanie (Frontiers in Veterinary Science, 2023)
Introduction Veterinary hemp products containing cannabidiol (CBD) and negligible psychoactive (THC) have increased popularity since hemp (with <0.3% THC) was removed from schedule 1 substances under the Controlled Substances Act in 2018. This was accompanied by increased CBD research, mostly on the short-term safety and efficacy for inflammatory and neurological conditions. It is imperative to understand how CBD is metabolized or accumulated in the body long-term, thus the goal of the present work was to determine monthly plasma CBD concentrations, as well as changes in pharmacokinetic (PK) parameters in chronically dosed dogs. Methods The study was a masked, placebo-controlled, randomized design. Six adult beagles were assigned to placebo, 5 and 10 mg/kg/day CBD treatment groups. Dogs received oral oil treatment once daily for 36 weeks. Blood was collected once every 4 weeks pre- and postprandially for CBD plasma determination (at 0 and 2 h). Pharmacokinetics were conducted at 0, 18 and 36 weeks. Pharmacokinetics and monthly CBD plasma data of dogs who received CBD were analyzed as repeated measures over time using a mixed model, with significance at α = 0.05. Results Average plasma CBD at 5 and 10 mg/kg were 97.3 ng/mL and 236.8 ng/mL pre-prandial, 341 ng/mL and 1,068 ng/mL postprandial, respectively. PK parameters suggested CBD accumulation over time, with significant increases in Cmax and AUC at both the 18 and 36-week timepoints. Cmax and AUC were dose proportional. Half-life demonstrated large inter-individual variations and increased (p < 0.05) at weeks 18 and 36 compared to baseline. Volume of distribution was not affected by time or treatment, while MRT increased, and clearance decreased over time (p < 0.05). Conclusions and clinical importance Chronic administration of CBD to healthy adult dogs led to a dose-proportional accumulation in the body for 36 weeks, which was confirmed by an increased half-life, total exposure, mean residence time and plasma peak. Our data also suggests that CBD plasma levels may have less daily variation if administered twice daily.